Total Risk Stock Investment: Does International Portfolio Diversification give more Impact to Investors? - Padmantyo, Sri; Prasojo, Prasojo (Prosiding University Research Colloquium, 2019)
Stock investment has become to be one of the most interesting andpromising ways to provide a faster rate of return compared to otherinvestments. Markowitz has set foundations about how to take a goodinvestment decision by considering its expected return and standarddeviation. The purpose of this research is two-fold. First, is tocompare the total portfolio risk between international and domesticportfolio diversification. Second, is to find the relationship betweenportfolio size and portfolio risk. This research applies mean-standarddeviations, paired t-test, and simple regression analysis on theAmerican, German, and Indonesian stock markets. The results showthat international diversification gives more significant total riskreduction compared to domestic one. Another results show asignificant relationship between portfolio size and risk reduction. Itmeans that the more number of stock in portfolio, the lesser risk thatwill be taken. The least risk can be achieved by holding 15 stockswhether in domestic or international portfolio diversification. Theresults have revealed that diversification has a positive impactthrough stock investment. This study strongly recommends todiversify the investment internationally and to increase the portfoliosize to gain the lower risk.